Demand response model based on improved Pareto optimum considering seasonal electricity prices for Dongfushan Island. (February 2021) - Wu, Xiaomin; Cao, Weihua; Wang, Dianhong; Ding, Min; Yu, Liangjun; Nakanishi, Yosuke
Abstract: In this paper, an improved optimization model is proposed for demand response in a remote off-grid microgrid local on the Dongfushan Island, China to develop the energy dispatch and economic benefits considering different electricity price under different seasonal meteorological conditions. First, the seasonal electricity pricing model is built with the power generation of renewable sources in different seasonal meteorological conditions. Second, satisfaction is evaluated by the seasonal electricity price and the power consumption pattern. Improved Pareto optimum based on a distributed learning algorithm is proposed to maximize the satisfaction so that the electricity bills of consumers are reduced and the profits of the retailer is increased. The performance of the proposed optimization model is validated in the HOMER software and Matlab. Simulation results show that the electricity bills of consumers are lower by using the proposed method. For the retailer, the generation cost saves 1216$, and the utilization of renewable energy increased by 3.9% in January 2011. Highlights: Efficiencies and economics of demand response are verified in an off-grid microgrid. A improve Pareto optimum is proposed to solving the demand response problem. Electricity price model based on different season meteorological is proposed. Reasonable control of flexible load to improve the efficiency of demand response. The economic benefits of retailers and consumers are improved under demand response.